2007
DOI: 10.1002/ejoc.200600852
|View full text |Cite
|
Sign up to set email alerts
|

Taking Up the Cudgels for Perchlorates: Uses and Applications in Organic Reactions under Mild Conditions

Abstract: Metal perchlorates are compounds of great chemical interest since they possess some unique properties, such as high electronegativity and relatively low charge density, poor complexing ability, high solubility in various organic solvents, and kinetic stability under mild conditions. Besides providing polar media when dissolved in solvents, metal perchlorates have recently found wide employment as Lewis acid promoters in various organic transformations, both in the development of new techniques for known and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…As a result of its manipulation ease, low‐cost, and benign character, the new iron catalyst described appears promising for large‐scale applications. It must be pointed out that perchlorate salts are stable under ordinary conditions of use 18. Furthermore, the use of hydrogen peroxide as oxidant is quite attractive, because it generates water as the only byproduct.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of its manipulation ease, low‐cost, and benign character, the new iron catalyst described appears promising for large‐scale applications. It must be pointed out that perchlorate salts are stable under ordinary conditions of use 18. Furthermore, the use of hydrogen peroxide as oxidant is quite attractive, because it generates water as the only byproduct.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the reaction mechanism, a plausible explanation is depicted in Scheme 3. In the presence of magnesium perchlorate, which is known to be able to coordinate 1,3bidentate compounds, [10] carbonyl derivative 9 rapidly condensed with the amine eliminating water and forming enamino derivative 1. Compound 1 added to ethyl propiolate (4) to give Michael adduct 11, as an intermediate, which underwent a second conjugate addition from 1 to give 12.…”
Section: Resultsmentioning
confidence: 99%
“…, 3.14(d, J = 1.4 Hz, 1 H), 3.87 (ddd, J = 4.5, 10.5, 1.5 Hz, 1 H), 4.10-4.25 (m, 6 H),6.14 (br. q, J = 1.5 Hz, 1 H),6.50-6.60 (m, 3 H), 7.13 (t, J = 8.0 Hz, 1 H),10.30 (br. s, 1 H) ppm.…”
mentioning
confidence: 99%
“…On the other hand, perchlorate salts of alkaline and alkaline earth metals showed to be very active in promoting a large variety of reactions, 18 in some cases being more powerful than metal triflates. 16b,17c,19 Concerning the risk connected with the use of such salts, it has been demonstrated that such perchlorates are not dangerous chemicals if not employed under highly acidic conditions and not exposed to high temperatures (>300-500°C).…”
mentioning
confidence: 99%